Soil fertility affected by land use history, relief position, and parent material under a tropical climate in NW-Vietnam - Gerhard Clemens (2018)
In Vietnam as much as half of the total land area is already degraded by soil erosion and nutrient depletion. In particular, degradation due to deforestation is increasingly affecting mountainous areas in north-western Vietnam. The necessity to safeguard the farmers' livelihoods requires sustainable resource management, which firstly requires a qualitative and quantitative evaluation of resources. The objectives of the present study were to (1) identify the dominant soil types and their vulnerability using elicitation of local soil knowledge, (2) characterise the physical and chemical properties of the soils and (3) link them to the relief position and land use in order to (4) initiate sustainable soil use based on recommendations deduced from objectives (1) to (3). These objectives were achieved also by the elicitation of local knowledge. The final aim of the study was to initiate sustainable soil use based on recommendations for sustainable land use scenarios. The Chieng Khoi commune in Son La province of northern Vietnam was chosen as representative for other erosion-prone Southeast Asian sloping areas. In a participatory approach, combining local and scientific knowledge, sixteen sites were selected, representative for distinct relief positions, parent material (sand stone and silt stone), land use history, and erosion hazard. Chemical (e.g. content of organic matter, nitrogen, cation exchange capacity, base saturation, and plant available phosphorous) and physical properties (e.g. air capacity, plant available water) were used to estimate soil fertility. The predominant reference soil groups in the study area are Alisols and Luvisols, with a high diversity in respect to soil fertility. These soils are locally named 'red soil' and 'black soil', respectively. Although the main physical processes are erosion and selective sedimentation, farmers tend to underestimate their impact and causes, whereas soil quality was well-evaluated. Soils with high fertility were found on less eroded upper parts of hills and at sites, where agricultural use started only recently. Once degraded by cultivation practices, soils derived from sandstone did not recover even after more than 50 years of fallow. As a result of unsustainable land use, soils on middle and lower slopes are often affected by severe soil erosion, whereas foot slope soils suffer from accumulation of eroded infertile subsoil material as well as stagnic conditions. This study showed that unsustainable land use at upslope landscape positions has a severe impact on downslope areas. The elicitation of local knowledge facilitated the identification of such hot spots, allowing the implementation of spatially targeted conservation measures. © 2010 Elsevier B.V. All rights reserved.